Fatal river drowning: the identification of research gaps through a systematic literature review. Issue 3 (4th January 2016) - Peden, Amy E; Franklin, Richard C; Leggat, Peter A
Abstract : Introduction: Drowning is a leading cause of unintentional death. Rivers are a common location for drowning. Unlike other location-specific prevention efforts (home swimming pools and beaches), little is known about prevention targeting river drowning deaths. Methods: A systematic literature review was undertaken using English language papers published between 1980 and 2014, exploring gaps in the literature, with a focus on epidemiology, risk factors and prevention strategies for river drowning. Results: Twenty-nine papers were deemed relevant to the study design including 21 (72.4%) on epidemiology, 18 (62.1%) on risk factors and 10 (34.5%) that proposed strategies for prevention. Risk factors identified included age, falls into water, swimming, using watercraft, sex and alcohol. Discussion: Gaps were identified in the published literature. These included a lack of an agreed definition for rivers, rates for fatal river drowning (however, crude rates were calculated for 12 papers, ranging from 0.20 to 1.89 per 100 000 people per annum), and consensus around risk factors, especially age. There was only one paper that explored a prevention programme; the remaining nine outlined proposed prevention activities. There is a need for studies into exposure patterns for rivers and an agreed definition (with consistent coding). Conclusions: This systematic review has identified that river drowning deaths are an issue in many regions and countries around the world. Further work to address gaps in the published research to date would benefit prevention efforts.